H1foo is essential for in vitro meiotic maturation of bovine oocytes. Issue 3 (June 2015) - Yun, Yan; An, Peng; Ning, Jing; Zhao, Gui-Ming; Yang, Wen-Lin; Lei, An-Min
Summary Oocyte-specific linker histone, H1foo, is localized on the oocyte chromosomes during the process of meiotic maturation, and is essential for mouse oocyte maturation. Bovine H1foo has been identified, and its expression profile throughout oocyte maturation and early embryo development has been established. However, it has not been confirmed if H1foo is indispensable during bovine oocyte maturation. Effective siRNAs against H1foo were screened in HeLa cells, and then siRNA was microinjected into bovine oocytes to down-regulate H1foo expression. H1foo overexpression was achieved via mRNA injection. Reverse transcription polymerase chain reaction (RT-PCR) results indicated that H1foo was up-regulated by 200% and down-regulated by 70%. Based on the first polar body extrusion (PB1E) rate, H1foo overexpression apparently promoted meiotic progression. The knockdown of H1foo significantly impaired bovine oocyte maturation compared with H1foo overexpression and control groups (H1foo overexpression = 88.7%, H1foo siRNA = 41.2%, control = 71.2%; P < 0.05). This decrease can be rescued by co-injection of a modified H1foo mRNA that has escaped from the siRNA target. However, the H1e (somatic linker histone) overexpression had no effect on PB1E rate when compared with the control group. Therefore we concluded that H1foo is essential for bovine oocyte maturation and its overexpression stimulates the process.